High VEGF Level is Produced by Human Umbilical Cord- Mesenchymal Stem Cells (hUC-MSCs) in Amino Acid-Rich Medium and under Hypoxia Condition - Veronika Maria Sidharta; Elizabeth Henny Herningtyas; Christine Ayu Lagonda; Dilafitria Fauza; Yuyus Kusnadi; Rina Susilowati; Ginus Partadiredja (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: Secretome production by stem cells depends on their culture conditions such as oxygen concentration and the composition of the culture media. In this study, we investigated the secretion of neurotrophic growth factors of human umbilical cord mesenchymal stem cells (hUC-MSCs) in amino acid-rich culture medium and under hypoxic condition.METHODS: hUC-MSCs were cultured in normoxic and various hypoxic (1%, 5%, 10%) conditions in an amino acid-rich culture medium. The end-point parameters (cell proliferation and survival, cell morphology and growth factor secretion) were measured at 3 time-points (48 hours, 72 hours and 96 hours). ELISA-based methods were used for neurotrophic factors detection, including neurotrophic growth factor (NGF), vascular endothelial factor (VEGF), and brain-derived neurotrophic factor (BDNF).RESULTS: NGF secretion was not detectable at any time points both in normoxia and hypoxia. BDNF secretion under normoxia was induced at 48 h time point and reached the highest level at an average of 181.9±13.01 pg/mL at 96 hours, whereas hypoxia exposure to hUC-MSCs only induced the BDNF secretion at low level. VEGF secretion was barely detectable in normoxic condition. However, VEGF secretion reached the highest level at an average of 7707.55±2110.85 pg/mL in 5% hypoxia at 96 hours.CONCLUSION: Combination of amino acid-rich culture medium and hypoxia condition dramatically induced high VEGF secretion by hUC-MSCs, especially at 5% hypoxia, induced mild BDNF secretion and had no effect toward NGF secretion.KEYWORDS: human umbilical cord mesenchymal stem cells, neurotrophic growth factor, amino acid-rich, hypoxia